Toll-Like Receptor 4-Deficient Mice Have Reduced Bone Destruction following Mixed Anaerobic Infection - Hou, Linda (American Society for Microbiology, 2000)
C3H/HeJ mice have an impaired ability to respond to lipopolysaccharide (LPS) due to a mutation in the gene that encodes Toll-like receptor 4 (TLR4). The effect of TLR4 deficiency on host responses to endodontic infections is unknown. In the present study, we compared periapical bone destruction, sepsis, and inflammatory cytokine production in LPS-hyporesponsive C3H/HeJ and wild-type control C3H/HeOuJ mice. The mandibular first molars of both strains were subjected to pulpal exposure and infection with a mixture of four anaerobic pathogens, Prevotella intermedia, Fusobacterium nucleatum, Streptococcus intermedius, and Peptostreptococcus micros. At sacrifice on day 21, TLR4-deficient C3H/HeJ mice had significantly reduced periapical bone destruction compared to wild-type C3H/HeOuJ mice (P < 0.001). The decreased bone destruction in C3H/HeJ correlated with reduced expression of the bone resorptive cytokines interleukin 1α (IL-1α) (P < 0.01) and IL-1β (P < 0.05) as well as the proinflammatory cytokine IL-12 (P < 0.05). No significant differences were seen in the levels of gamma interferon, tumor necrosis factor alpha (TNF-α), or IL-10 between the two strains. The expression of IL-1α, IL-1β, TNF-α, IL-10, and IL-12 were all significantly reduced in vitro in macrophages from both TLR4-deficient C3H/HeJ and C57BL/10ScNCr strains, compared to wild-type controls. Notably, the responses of TLR4-deficient macrophages to both gram-positive and gram-negative bacteria were similarly reduced. Neither C3H/HeJ nor C3H/HeOuJ mice exhibited orofacial abscess development or infection dissemination as determined by splenomegaly or cachexia. We conclude that intact TLR function mediates increased proinflammatory responses and bone destruction in response to mixed anaerobic infections.